Aconitum Napellus: Detoxification and Acute Toxicity Investigation Followed by Sub-Acute Toxicity and Bioavailability Assessment of Highest and Lowest LD50 Extract. Issue 2 (4th March 2019) - Shoaib, Ambreen; Badruddeen,; Siddiqui, Hefazat Hussain; Dixit, Rakesh Kumar; Akhtar, Juber
Abstract: In spite of high toxicological risk Aconitum napellus (ACON) is tremendously used for the treatment of rheumatoid and joint pain. The acute toxicity study was assessed for cow milk treated (CMT), goat milk treated (GMT) and water treated (WT) extracts of Aconitum napellus (ACON) in mice, expressed as LD50 (25, 50, 10 and 5 mg/kg respectively). The sub-acute toxicity of ACON (0.5 mg/kg/day) and GMT (5 mg/kg/day) were also performed in SD-rats for 28 days. The GMT not showed any treatment related changes, however ACON produced significant clinical changes in mean corpuscular volume and mean corpuscular hemoglobin level. Moreover creatinine, bilirubin, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase levels significantly increased ( p < 0.001), and abnormal histoarchitecture of kidney and liver were also observed as compared to control . In vivo pharmacokinetic study also confirmed that GMT constituted lesser amount of aconitine (Cmax = 1.84±1.98) than standard aconitine (Cmax = 6.82±3.1) and ACON (Cmax = 4.62±2.2). Moreover dose of GMT revealed 10 times safer than ACON. Overall processed ACON not produced any sign of toxicity at a dose dependent manner.